2009
DOI: 10.1093/eurheartj/ehp160
|View full text |Cite
|
Sign up to set email alerts
|

Excessive heart rate increase during mild mental stress in preparation for exercise predicts sudden death in the general population

Abstract: An important heart rate increase produced by a mild mental stress predicts long-term risk for sudden cardiac death. Heart rate changes before an exercise test may provide a simple tool for risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The identification of those in the population who are at higher risk of sudden death remains a major challenge, as nearly half of the victims are asymptomatic, and successful resuscitation outside a hospital is rare. We and others previously reported significant associations between traditional and nontraditional risk factors with sudden death, [3][4][5][6][7][8][9] but these factors are not sufficiently sensitive to identify those who are at higher risk. Therefore, new risk markers need to be investigated.…”
mentioning
confidence: 76%
“…The identification of those in the population who are at higher risk of sudden death remains a major challenge, as nearly half of the victims are asymptomatic, and successful resuscitation outside a hospital is rare. We and others previously reported significant associations between traditional and nontraditional risk factors with sudden death, [3][4][5][6][7][8][9] but these factors are not sufficiently sensitive to identify those who are at higher risk. Therefore, new risk markers need to be investigated.…”
mentioning
confidence: 76%
“…Moreover, these variability criteria are computed for the entire ECG-Holter recordings, regardless of the duration and concomitant activities and stresses the subjects experience. We have previously shown in the Paris Prospective Study I that HR at rest, during exercise and recovery, and during mental stress were associated with total mortality and sudden death in particular [5][6][7]. With the contemporary PPS3, these specific periods will be studied more in depth to propose novel heart rate parameters of potential interest.…”
Section: Discussionmentioning
confidence: 98%
“…Imbalance between the sympathetic and the vagal tone is suggested to be the main underlying mechanism related to sudden death susceptibility [4]. For example, through the Paris Prospective Study I, our group previously showed that heart rate (HR) at rest, just before exercise and during or after an exercise test was a particular strong and specific marker of sudden death risk compared to non-sudden coronary death [5][6][7]. However, these results, which mostly reflect the effect of one single HR measure, were obtained in men only and concerned baseline measurements that were performed in the late 60's, before the era of beta blocking agents.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, sudden centrally mediated sympathetic activation elicits a mostly localized release of norepinephrine from neural terminals, which increases both regional heterogeneity and cardiac electrical instability. This explains the profound difference in the correlation between sudden death and HR responses during exercise and mental stress 23 . Thus, it had to be expected that uniform beta-adrenergic stimulation by isoproterenol perfusion would reduce the dispersion of repolarization caused by anthopleurin (which augments late I Na ), and that this “beneficial” effect produced by stimulation of beta-adrenergic receptors would be prevented by propranolol, a drug whose function is blocking the beta-receptors.…”
Section: Discussionmentioning
confidence: 99%